2009
DOI: 10.1111/j.1540-8183.2009.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Redundant Protective Barriers: Minimizing Operator Occupational Risk

Abstract: The optimal use of combined personal and movable (redundant) lead barriers results in a significant reduction in total-body operator radiation exposure in the catheterization laboratory. The use of redundant barriers in the catheterization suite is associated with a dramatic theoretical long-term occupational risk reduction and should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The efficacy of protective eyewear is also found to be very sensitive to other factors such as the angular position of the radiologist. Research by Challa speculated that the overall dose reduction during a procedure could be much lower than expected, since the parameters involved in practical use are much more complicated than that in calibration. It is found in our study that due to the gap between the two lenses of the glasses, the DRF is much higher for the left lens than that for the right lens when the irradiated area is on the left side of the radiologist.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of protective eyewear is also found to be very sensitive to other factors such as the angular position of the radiologist. Research by Challa speculated that the overall dose reduction during a procedure could be much lower than expected, since the parameters involved in practical use are much more complicated than that in calibration. It is found in our study that due to the gap between the two lenses of the glasses, the DRF is much higher for the left lens than that for the right lens when the irradiated area is on the left side of the radiologist.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing 10 lens types, including lenses capable of attenuating a direct X-ray beam [1000 times in phantom studies, one study found that lens irradiation during patient fluoroscopy was reduced at best by a factor of 5.3 [55]. Challa found that eyeglasses reduced lens dose in cardiology procedures to the left and right eye by 67 and 45 %, respectively [56], and a similar cardiology study found a left eye dose reduction of only 35 % [57]. Another study assessed eyeglass protection in a wide range of interventional procedures, finding a dose reduction factor of 2.1 for the left (tube-side) eye and no significant dose reduction for the right eye [52].…”
Section: Techniques For Minimizing Lens Exposurementioning
confidence: 98%
“…Challa et al 41 In vivo, IC, n = 1 Rectangular 3 (L); 1.8 (R) Dash et al 42 In vivo, IC, n = 2 Rectangular, no lateral protection 1.5 (L)…”
Section: Studymentioning
confidence: 99%